Business Models For Sustainable Technology: Strategic Re-Framing And Business Model Schema Change In Internal Corporate Venturing - Reuter, Emmanuelle; Tao Krauspe (My University, 2022)
Established firms often develop new businesses through internal corporate venturing (ICV), for instance, to capture value from novel sustainable technologies. We illuminate the early definition stage of ICV’s by asking: When and how business model schemas—that is, managerial understandings of how value is created and captured—change in ICV? We conduct a qualitative, embedded case study of the change in a business model schema for e-mobility in a Swiss utility’s ICV. We uncover a key trigger: strategic re-framing—the active re-formulation of the definition of a given situation within ICV–top manager interactions. The strategic re-framing’s specificity level provokes either schema restrictions or expansions via the distinct accommodation practices it induces. Our theoretical model of business model schema change contributes to the literatures on managerial cognition, business models, and ICV, suggesting that business model schema change in ICV is a semi-autonomous process that involves both independent and joint endeavors.